Проблеми інтелектуально-кадрового забезпечення IT-сфери України - Старкіна, О. Д.; Starkina, O.; Яковенко, Р. В.; Yakovenko, R. (Ексклюзив-Систем, 2018)
Визначено тенденції розвитку інноваційної економіки в Україні та заходи підтримки державою інноваційно-кадрового забезпечення інноваційних кластерів. The tendencies of development of innovative economy in Ukraine and measures of state support of innovation and personnel provision of innovative clusters are determined.
Problems of intellectual and personnel support of IT-sphere of Ukraine
Keywords: інноваційна економіка; інтелектуально-кадрове забезпечення; кластер; ІТ-сфера; innovative economy; intellectual and personnel support; cluster; IT-sphere